(untitled) (Transport systems and technologies, 2024)
The overwhelming majority of compartment cars owned by Ukrzaliznytsia JSC were manufactured in Germany in the 70-80s of the last century. They have exhausted their resource. The metal structures of the frame and body are badly worn. Extending the service life of such cars requires a thorough study of the possibilities of their further use. The article discusses the results of an analysis of the stress-strain state of passenger car bodies. A three-dimensional model of the body was built. Body strength calculations were performed using the finite element method using the ANSYS software package. The racks and upper trim of the side walls, roof arches, etc. were considered as rods. The body frame, substructure, side wall cladding, end walls, roof cladding and floor deck were modeled using plate finite elements. Calculations were carried out in accordance with the requirements of current regulatory documents. The maximum speed was assumed to be 160 km/h. The developed model was verified. The results obtained were compared with the results of experimental studies (strength tests). The similarity of the results confirmed the correctness of the created model. A study was carried out of the stress-strain state of the body at nominal sizes with standard skin thicknesses. It has been established that the stresses arising in the most loaded areas do not exceed the permissible values for structural steels. The resulting model of the body will subsequently make it possible to determine the wear limits of the load-bearing structures of the frame and body. It also allows, using the calculation-probabilistic method, taking into account the probabilistic nature of all existing loads, to calculate the reliability indicators of the car and its final life.